Survey of Numerical Analysis for Fractional Integro-Differential Equations - Hamood, Maha M.; Ghadle, Kirtiwant P. (Discontinuity, Nonlinearity, and Complexity, 2026)
As a result of the study carried out over the previous three decades, fractional calculus has become much more essential due to its broad use in science and engineering. Fractional derivatives and integrals can be used to explain the properties of memory and inheritance. Therefore, there is a growing demand to develop the various numerical methods for solving linear and nonlinear fractional integro-differential equations. In this essay, we reviewed the literature on basic ideas, analytical strategies and several numerical methodologies for solving linear and nonlinear fractional integro differential equations.